2016
DOI: 10.1007/s40501-016-0075-8
|View full text |Cite
|
Sign up to set email alerts
|

Treating Negative Symptoms in Schizophrenia: an Update

Abstract: Opinion StatementInterest in the negative symptoms of schizophrenia has increased rapidly over the last several decades, paralleling a growing interest in functional, in addition to clinical, recovery, and evidence underscoring the importance negative symptoms play in the former. Efforts continue to better define and measure negative symptoms, distinguish their impact from that of other symptom domains, and establish effective treatments as well as trials to assess these. Multiple interventions have been the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
101
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 140 publications
(105 citation statements)
references
References 119 publications
2
101
1
1
Order By: Relevance
“…In previous reports, 41% of patients experienced two or more negative symptoms [41], while as many as 58% had at least one negative symptom [42]. The impact of negative symptoms on overall functional impairment is substantial and no specific treatment can be considered particularly effective against these symptoms, according to the evidence base summarised in a recent review [43]. Negative symptoms of schizophrenia may pose a particular burden to patients, due to their links to lower quality of life and reduced social contact – a recent study, which also used the EuroSC cohort, showed that social isolation in patients with schizophrenia is associated with poor psychosocial functioning and low quality of life (QoL) [21].…”
Section: Discussionmentioning
confidence: 99%
“…In previous reports, 41% of patients experienced two or more negative symptoms [41], while as many as 58% had at least one negative symptom [42]. The impact of negative symptoms on overall functional impairment is substantial and no specific treatment can be considered particularly effective against these symptoms, according to the evidence base summarised in a recent review [43]. Negative symptoms of schizophrenia may pose a particular burden to patients, due to their links to lower quality of life and reduced social contact – a recent study, which also used the EuroSC cohort, showed that social isolation in patients with schizophrenia is associated with poor psychosocial functioning and low quality of life (QoL) [21].…”
Section: Discussionmentioning
confidence: 99%
“…Motivational deficits in patients with schizophrenia are persistent, are prevalent from the earliest stages of the disease, and may uniquely predict outcomes beyond other symptoms . Across several neuropsychiatric disorders, including schizophrenia, amotivation is associated with abnormal functioning of frontal‐striatal circuits involving the dorsolateral prefrontal cortex, anterior cingulate cortex, and ventral striatum (VS) .…”
Section: Introductionmentioning
confidence: 99%
“…Their therapeutic benefit is assumed to be related to the blockade of D 2 receptors in the ventral striatum (nucleus accumbens). On the other hand, these compounds are not efficacious against the negative symptoms which may even aggravate (Millan et al, 2014; Remington et al, 2016). These drugs also induce several serious side-effects, either due to their off-targets including H 1 , α 2 , muscarinic2 (M 2 ) receptor antagonist properties, or to chronic central D 2 receptor blockade.…”
Section: From the Drugs To Monoaminesmentioning
confidence: 99%
“…The negative symptoms remain one of the most difficult challenges in the treatment of schizophrenia (Millan et al, 2014; Remington et al, 2016). Interestingly, neuropsychopharmacological analysis tends to dissociate various symptoms of schizophrenia which could have distinct etiology (Buckley et al, 2009).…”
Section: From the Drugs To Monoaminesmentioning
confidence: 99%